Development of cryogenic alpha spectrometers using metallic magnetic calorimeters - Ranitzsch, Philipp; Kempf, Sebastian; Pabinger, Andreas; Pies, Christian; Porst, J. -P.; Schäfer, Stefan; Fleischmann, Andreas; Gastaldo, Loredana; Enss, Christian; Jang, Y. S.; Kim, I. H.; Kim, M. S.; et al. (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2011)
Cryogenic particle detectors have recently been adopted in radiation detection and measurement because of their high energy resolution. Many of these detectors have demonstrated energy resolutions better than the theoretical limit of semiconductor detectors. We report the development of a micro-fabricated magnetic calorimeter coupled to a large-area particle absorber. It is based on a planar, 1mm2 large paramagnetic temperature sensor made of sputtered Au:Er, which covers a superconducting meander-shaped pickup coil coupled to a low-noise dc-SQUID to monitor the magnetization of the sensor. A piece of gold foil of 2.5×2.5×0.07mm3 was glued to the Au:Er film to serve as an absorber for incident alpha particles. The detector performance was investigated with an 241Am source. The signal size comparison for alpha and gamma peaks with a large difference in energy demonstrated that the detector had good linear behavior. An energy resolution of 2.83±0.05keV in FWHM was obtained for 5.5MeV alpha particles.